Depressive Profiles among Older Puerto Rican Adults - Rostant, Ola S.; Poggi, Angedith (Puerto Rico Health Sciences Journal, 2023)
Objectives: This study examines the heterogeneity of depressive symptoms among older adults residing on the Island of Puerto Rico and their association with risk and protective health factors. Methods: Data from the Puerto Rican Elderly: Health Conditions study (PREHCO) to identify risk and protective factors associated with profiles of depressive symptoms. The sample was comprised of 3,114 Puerto Rican older adults ages 60 to 102 (71 ± 8.2 SD). The Geriatric Depression Scale 15-item short form (GDS-15) was used to assess the presence of depressive symptoms. Latent class analysis (LCA) was used to categorize depressive symptom classes. The association between depressive symptom classes and health status, lifestyle, health behavior and demographic characteristics were evaluated. Results: A three-class model was identified, they were defined as “low depressive symptoms” (56%), “medium depressive symptoms” (31%), and “high depressive symptoms” (13%). Having chronic illnesses, mainly diabetes, heart disease and high blood pressure as well as a history of smoking, and poor self-rated vision were all associated with being in a higher depressive class. Exercising regularly and participating in volunteer activities were protective to being in a high depressive class. Conclusion: Chronic illnesses and poor self-rated vision were associated with being in a higher depressive classification. These findings can inform targeted interventions for sub-groups of community dwelling older adults impacted by depression.